Characterization of a‐SiNx:H layer: Bulk properties, interface with Si and solar cell efficiency. Issue 4 (26th November 2012) - Lamers, Machteld; Butler, Keith; Vullum, Per Erik; Harding, John; Weeber, Arthur
Abstract In this paper two front‐side a‐SiNx:H layers that can be used in the solar cell industry are extensively characterized and related to solar cell efficiency. Variations in layer build up, atomic density, optical properties, bulk passivation and surface passivation are discussed. The build up of these two layers are considered against a background of over 80 SiNx:H layers. These layers differ in stoichiometry, atomic content, optical properties and surface passivation, as the refractive index is varied between 1.8 and 3.0. Additionally, comparable data output of different characterization equipment is discussed on validity. On solar cells, the effect of different layer build up is investigated and it is found that a wide process window is allowed for similar cell efficiencies regarding the optical transmission, bulk and surface passivation.